2006
DOI: 10.1016/j.eurpsy.2005.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress reactions of children and adolescents exposed to the Athens 1999 earthquake

Abstract: This study was undertaken 6-7 months after the 1999 Athens earthquake with the aim of exploring the differences in post-traumatic stress disorder (PTSD), anxiety and depression symptoms between a group of children exposed to earthquake with a group of children not exposed to it, but with both groups potentially exposed to the same levels of post-earthquake adversities. The study included 2037 children, aged 9-17 years, who were assessed with self-completed questionnaires. The directly exposed group (N=1752) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
138
6
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(164 citation statements)
references
References 19 publications
(27 reference statements)
18
138
6
2
Order By: Relevance
“…Posttraumatic stress disorder (PTSD) is one of the most studied negative outcomes in trauma-focused research (Fan, Long, Zhou, Zheng, & Liu, 2015; Giannopoulou et al, 2006). Youth are at particularly high risk of being exposed to traumatic events (Lieberman & Van Horn, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Posttraumatic stress disorder (PTSD) is one of the most studied negative outcomes in trauma-focused research (Fan, Long, Zhou, Zheng, & Liu, 2015; Giannopoulou et al, 2006). Youth are at particularly high risk of being exposed to traumatic events (Lieberman & Van Horn, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When comparing girls and boys, previous studies have shown that girls are more likely than boys to develop PTSD symptoms following disaster exposure (Garrison et al, 1995; Giannopoulou et al, 2006; John et al, 2007), although some studies find no such difference (Catani et al, 2008). We did not compare girls and boys regarding prevalence of symptoms, but our gender stratified analyses indicate that both genders show increased risk of symptoms of anxiety or worries but only boys show headache(s) and sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to predictive factors, some studies have found girls to be more likely than boys to show symptoms of post-traumatic stress following disasters (Garrison et al, 1995; Giannopoulou et al, 2006; John et al, 2007; Lai et al, 2013), while others have found no gender specific effects (Catani et al, 2008). In addition, research has indicated that experiencing secondary life stressors such as loss of home, having to change schools and shifts in parental employment and finances should increase the risk of adverse mental health outcomes among children post-disaster (Fan et al, 2011; La Greca et al, 2010; Silverman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This was a 5.9 Richter earthquake followed by 4000 aftershocks, had its epicentre in the north-western outskirts of Athens and was the most devastating in last 50 years, as it resulted in 143 deaths, more than 400 injuries and damage to 74,067 households. All studies found high rates of PTSS in the earthquake exposed group 4–6 months following the event compared to indirectly exposed (Giannopoulou et al, 2006) or non-exposed (Kolaitis et al, 2003) groups.…”
Section: Current Research In Greecementioning
confidence: 96%
“…The 1999 Athens earthquake is the most studied natural disaster in Greece in terms of the psychosocial effects on children, adolescents and adults (Giannopoulou et al, 2006; Goenjian et al, 2011; Groom & Soureti, 2004; Kolaitis et al, 2003; Roussos et al, 2005). This was a 5.9 Richter earthquake followed by 4000 aftershocks, had its epicentre in the north-western outskirts of Athens and was the most devastating in last 50 years, as it resulted in 143 deaths, more than 400 injuries and damage to 74,067 households.…”
Section: Current Research In Greecementioning
confidence: 99%